2018
DOI: 10.1186/s13014-018-1035-9
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic role of hemoglobin levels in patients undergoing concurrent chemo-radiation for anal cancer

Abstract: BackgroundConcurrent chemo-radiation (CT-RT) is a standard therapy for squamous cell carcinoma of anal canal. Different clinical and biological factors may potentially affect outcome. We investigated the prognostic role of baseline hemoglobin (Hb) in a cohort of anal cancer patients submitted to CT-RT with 5-fluorouracil and mitomycin C.MethodsUp to 161 patients with clinical stage T1-T4/N0-N3/M0 were treated. Response was assessed at 6 weeks and thereafter at 3, 6 and 12 months. Two different approaches were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
30
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 25 publications
3
30
1
Order By: Relevance
“…In multivariate analysis, pre-treatment Hb level was significantly correlated with OS (p=0.001) but not with PFS (p=0.12). [29] In our study, similar results were obtained among all the hematological parameters, only pre RT Hb levels significantly correlated with OS but not with PFS. PFS and local control (LC) were significantly increased in patients with low pre-RT CEA.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In multivariate analysis, pre-treatment Hb level was significantly correlated with OS (p=0.001) but not with PFS (p=0.12). [29] In our study, similar results were obtained among all the hematological parameters, only pre RT Hb levels significantly correlated with OS but not with PFS. PFS and local control (LC) were significantly increased in patients with low pre-RT CEA.…”
Section: Discussionsupporting
confidence: 86%
“…As a result, the 5-year OS and DFS rates were 85% and 86% for patients with low CEA levels, 73% and 79% for patients with high CEA levels, respectively. [28] Franco et al [29] assessed the prognostic role of hemoglobin levels in 161 patients with anal cancer who underwent CRT. In multivariate analysis, pre-treatment Hb level was significantly correlated with OS (p=0.001) but not with PFS (p=0.12).…”
Section: Discussionmentioning
confidence: 99%
“…Serum albumin is one of the most important indicators of nutritional status, and it is an independent prognostic indicator in various malignancies, such as gastric cancer,30 colorectal cancer,31 breast cancer,32 ovarian cancer33 and cervical cancer 34. Hemoglobin is a clinical characteristic that is a prognostic indicator in various malignancies, such as anal cancer35 and head and neck cancer 36,37. It was hypothesized that anaemia may enhance tumor hypoxia and increase tumor cell resistance to therapy to promote distant metastasis 3537.…”
Section: Discussionmentioning
confidence: 99%
“…Hemoglobin is a clinical characteristic that is a prognostic indicator in various malignancies, such as anal cancer35 and head and neck cancer 36,37. It was hypothesized that anaemia may enhance tumor hypoxia and increase tumor cell resistance to therapy to promote distant metastasis 3537. Franco et al reported that preoperative hemoglobin level was an independent prognostic indicator for OS, but not PFS 35.…”
Section: Discussionmentioning
confidence: 99%
“…Mature data coming from the ACT-I trial suggested that palpable lymph nodes and male sex can be considered as prognostic factors for loco-regional recurrence and overall survival. The same trial and a confirmatory retrospective analysis showed that a low baseline hemoglobin level is able to predict for cancer-related death and death from any cause (5,7). The positivity to Human Papilloma Virus infection has also been shown to predict for overall and disease-specific survival (8).…”
mentioning
confidence: 97%